2023
DOI: 10.3389/fnins.2023.1074439
|View full text |Cite
|
Sign up to set email alerts
|

Integration of neuromorphic AI in event-driven distributed digitized systems: Concepts and research directions

Abstract: Increasing complexity and data-generation rates in cyber-physical systems and the industrial Internet of things are calling for a corresponding increase in AI capabilities at the resource-constrained edges of the Internet. Meanwhile, the resource requirements of digital computing and deep learning are growing exponentially, in an unsustainable manner. One possible way to bridge this gap is the adoption of resource-efficient brain-inspired “neuromorphic” processing and sensing devices, which use event-driven, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 109 publications
0
5
0
Order By: Relevance
“…In traditional computing systems, individual components, such as transistors, can fail causing large portions of the system to malfunction. However, in neuromorphic hardware, multiple artificial neurons and synapses are used to perform the same function [29]. This redundancy helps build resilience to systems failing.…”
Section: Neuromorphic Hardwarementioning
confidence: 99%
“…In traditional computing systems, individual components, such as transistors, can fail causing large portions of the system to malfunction. However, in neuromorphic hardware, multiple artificial neurons and synapses are used to perform the same function [29]. This redundancy helps build resilience to systems failing.…”
Section: Neuromorphic Hardwarementioning
confidence: 99%
“…Datasets for neuromorphic vision sensors include (Zhu et al, 2018;Pfeiffer et al, 2022;Nilsson et al, 2023) for tasks like depth estimation and visual odometry. Using DAVIS346 to record a significant number of autopilot and UAV scenes, Zhu et al (Zhu et al, 2018) revealed the MVSEC dataset for stereo vision, which is extensively used in the field of neuromorphic vision.…”
Section: Real Datasetmentioning
confidence: 99%
“…Using DAVIS346 to record a significant number of autopilot and UAV scenes, Zhu et al (Zhu et al, 2018) revealed the MVSEC dataset for stereo vision, which is extensively used in the field of neuromorphic vision. A DAVIS240 and an Astra depth camera mounted on a mobile robot were used to record interior scenes in (Nilsson et al, 2023) large-scale multimodal LMED dataset. For the SLAM problem, Pfeiffer et al (Pfeiffer et al, 2022) created a UZH-FPV dataset with built-in information such as DAVIS346 pulse flow, APS image, optical flow, camera posture, and route (Paredes et al, 2019).…”
Section: Real Datasetmentioning
confidence: 99%
“…Event-driven data-flow computation, inspired by the sparse spiking activities in cortical networks (Wolfe et al, 2010 ), is the primary computing paradigm in the majority of neuromorphic processors (Nilsson et al, 2023 ). It takes advantage of the sparsity in neural activation (spikes) to skip redundant operations.…”
Section: Introductionmentioning
confidence: 99%